Identifying and prioritizing the factors of service experience in banks: A Best-Worst method - Shahrbanoo Yadollahi; Ali Kazemi; Bahram Ranjbarian (Decision Science Letters, 2018)
The present study aimed at identifying and evaluating the factors affecting the service experience at the touch points of banking services. These factors were prioritized to help the managers understand the most important factors for achieving the favorable service experience. In this study, the theoretical foundations and interviews with customers were used to identify the factors forming the service experience at touch points. Then, the Best-Worst method (BMW) was used to evaluate and determine the significance of each identified factor. Sixteen customers participated in the interview and ten customers participated in the study by the BMW method. Six touch points and 34 factors forming the service experience were created at these points of interview analysis. The research findings showed that ‘service process’ and ‘interaction customer-employees’ for creating a favorable experience are significant in banking services. In addition, the findings showed that bank managers should allocate their resources for improving them to achieve the competitive advantage.